PDF4LHC recommendations for LHC Run II - Butterworth, Jonathan; Carrazza, Stefano; Cooper-Sarkar, Amanda; Roeck, Albert De; Feltesse, Joël; Forte, Stefano; Gao, Jun; Glazov, Sasha; Huston, Joey; Kassabov, Zahari; McNulty, Ronan; Morsch, Andreas; et al. (Journal of physics. G, Nuclear and particle physics, 2016)
We provide an updated recommendation for the usage of sets of parton distribution functions (PDFs) and the assessment of PDF and PDF+ uncertainties suitable for applications at the LHC Run II. We review developments since the previous PDF4LHC recommendation, and discuss and compare the new generation of PDFs, which include substantial information from experimental data from the Run I of the LHC. We then propose a new prescription for the combination of a suitable subset of the available PDF sets, which is presented in terms of a single combined PDF set. We finally discuss tools which allow for the delivery of this combined set in terms of optimized sets of Hessian eigenvectors or Monte Carlo replicas, and their usage, and provide some examples of their application to LHC phenomenology. This paper is dedicated to the memory of Guido Altarelli (1941-2015), whose seminal work made possible the quantitative study of PDFs.
Gesehen am 28.04.2020